Exposure of polycyclic aromatic hydrocarbon on potential health risks and genotoxicity outcomes among primary school children in the vicinity of petrochemicals area - Sopian, Nor Ashikin (2020)
Prolonged exposure to polycyclic aromatic hydrocarbons (PAHs) air pollutants may increase the risk of developing cancer and multiple acute respiratory health problems, especially children who live near heavy industries. Moreover, the air pollutants emitted from the industry had been frequently associated with genetic defects among children. This study aimed to evaluate the association of particulate PAHs exposure on potential genotoxicity among primary school children living close to the petrochemical industry and comparative group in Terengganu. A validated questionnaire on socio-demographic, dietary, health status, and personal exposure was distributed to randomly selected children. The indoor and outdoor samples of fine particulate matter (PM2.5) bound to PAHs were collected on quartz fibre filters using a MiniVol portable air sampler, for 24h. The 16s priority PAHs concentration was quantified using Gas Chromatography-Mass Spectrometer. Source diagnostic ratio was applied to determine the source of PAHs emission. Meanwhile, the biomarker of PAHs exposure, which is urinary 1-hydroxypyrene (1-OHP), was determined by a High Performance-Liquid Chromatography, with fluorescence detector. The formation of micronucleus (Mn) and DNA damage in the buccal cell were evaluated using Micronucleus Assay and Comet Assay. The results showed that the outdoor total 16s priority PAHs concentration was higher (range between 7.18 to 67.72 ng/m3) than the indoor environments (range between 3.45 to 63.22 ng/m3). These concentrations were obviously higher at the exposed school as compared to the comparative schools. Based on the source diagnostic ratio, the PAHs of the exposed school are pyrogenic, which mainly originated from high combustion activities (vehicle and industrial emissions). Meanwhile, the urinary 1-OHP concentration was significantly higher among the exposed children than the comparative group (0.25 vs 0.14 μmol/mol-creatinine). The Mn frequency and DNA damage were also considerably higher among the exposed children as compared to the comparative group. Significant associations were observed between ii environmental PAHs exposure with urinary 1-OHP, Mn frequency, and DNA damage. Children in the industrial area had 3 to 6 higher risk of DNA damage, and 2 to 7 times higher risk of chromosomal damage. According to the Incremental Lifetime Cancer Risk (ILCR) model, the average cancer risk for the exposed and comparative children was 9.95E-07 and 1.80E-07, respectively. The result from Multiple Linear Regression shows the concentration of total PAHs, the total carcinogenic PAHs, and open burning practice were the most significant factors associated with the Mn frequency and DNA damage in children, after controlling the possible confounders. This study reveals that the children who reside nearby the industry and frequent open burning were exposed to higher concentration air pollutants as compared to the comparative group. The higher exposure had increased the risk of genotoxic effect and cancer risk among a vulnerable group like children. This finding indicates that there is a need for industrial management to monitor and control emissions from industrial activity actively. Besides, it also assists the authorities in the formulation of strategic guidelines for air quality management at the primary school and establishing the safe level of air pollutants exposure in the microenvironment.